Relocating Stevenson: From a Victorian to a post/modern world - Azer Banu Kemaloğlu (Literacy Trek, 2020)
Robert Louis Stevenson's novella, The Strange Case of Dr. Jekyll and Mr. Hyde (1886) appears to be a Victorian novel. Yet, the highly acclaimed novella experiments with traditional concept of dualism and rejects the notion of dependent entities within a single body. Stevenson portrays two separate bodies embodying two separate attributes of human beings constantly in fight over power. This power relationship is reinforced by the fragmented spaces depicted by the novelist. Dr. Jekyll's decentred house with two ambiguous entrances is read as an extension of his fragmented body in a postmodern context. In this respect, the novella suggests possibilities, impossibilities and multiplicities in terms of geographical, temporal and cultural experiences. Stevenson attempts to show how modernist assumptions about the perfectibility of mankind are perverted as the novella rejects the relationship between reality and appearance celebrating a postmodern duality. Taking from Frederick Jameson's argument that postmodernism rejects essence versus reality, the aim of this paper is to examine the fluctuations of Stevenson's place in Victorian, modernist and postmodernist ideologies. Since there is no fixed reference or stability in postmodern condition or postmodern temporality, Stevenson challenges the values of Western culture and belief as a whole. As a consequence, the fragmented selves of a single body and multiple narratives of the novel further explicate the fragmented place of Stevenson within a single ideology and condition.